Pengaruh Boikot terhadap Minat Beli Produk Pesaing di Kota Sampit - Azizah, Windy Nur; Andriyati, Yuli (Universitas Darwan Ali, 2025)
The boycott movement was widely discussed at the end of 2023. People began boycotting products that directly or indirectly supported acts of genocide. The impact of this boycott became increasingly evident on the targeted products. This study aims to examine the effect of the boycott of Israeli products on the purchase intention of competing products that were not boycotted. The study population consists of all residents of Sampit City. The sample was selected using purposive sampling, and the sample size was determined using Lemeshow's formula, resulting in 100 respondents. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression. The results of the study show that the boycott has a positive effect on the purchase intention of competing products. Additionally, religion also has a positive effect in strengthening the relationship between the boycott and purchase intention. The boycott encouraged people to switch to alternative products, leading to a higher demand for substitute goods. Initially, many people were accustomed to using the boycotted products, but over time, they gradually transitioned to non-boycotted products, most of which are locally made. This trend is particularly evident in Indonesia, where the majority of the population is Muslim.